EFL teachers’ identity in self-directed learning: A work-from-home phenomenology - Ashadi Ashadi; Erna Andriyanti; Widyastuti Purbani; Ihtiara Fitrianingsih (Universitas Syiah Kuala, 2022)
Major potential effects of abrupt changes in educational settings particularly for education stakeholders such as teachers have been somewhat interesting to examine. This study examines how teachers of English as a Foreign Language (EFL) in different schooling levels acclimatize their experiences due to the unanticipated Covid-19 outbreak, which forced them to pursue Online Distance Learning (ODL). Employing a phenomenological approach, eight teachers from various educational and psychometric backgrounds in three different provinces in Indonesia shared their experiences in coping with the changes. Before engaging in two semi-structured interviews, they were invited to complete an e-reflection to share their feelings, concerns, difficulties, and challenges. To get to the core of their experience, the data were scrutinized following an interpretive phenomenological analysis which includes an early focus on the lines of inquiry, central concerns and important themes, identification of shared meanings, final interpretations, and the dissemination of the interpretations. The findings demonstrated that the changes created an ambivalent experience of being challenged and bored, prompting teachers to reflect on their existing practice and respond appropriately by combining empathy, new roles, and technology paramount through their self-directed learning (SDL). Further implications on teacher agency and identity are discussed to shed light on the reshaping of teacher identities due to ODL and SDL.